Effects of pre-eclampsia on corneal tomography and specular microscopy parameters: A prospective study (Annals of Medical Research, 2025)
Aim: To evaluate the effect of preeclampsia on corneal tomography and specular microscopy parameters.Materials and Methods: A total of 22 preeclamptic women were evaluated prospectively. Patients were evaluated at prepartum and postpartum third months. Best-corrected visual acuity (BCVA), intraocular pressure (IOP), slit lamp, optical coherence tomography, corneal tomography, and specular microscopy were recorded and compared.Results: Prepartum BCVA was 0.065±0.638 logMAR, and postpartum BCVA was 0.050±0.823 logMAR, which was significantly different (p=0.033). The mean spherical equivalent was -0.68±1.27 diopter at prepartum and 0.00±1.41 diopter at postpartum period (p
Keywords: Corneal tomography; Intraocular pressure; Preeclampsia; Pregnancy; Specular microscopy